A comparative study on complete and implant retained denture treatments – A biomechanics perspective. Issue 3 (5th February 2015) - Chen, Junning; Ahmad, Rohana; Suenaga, Hanako; Li, Wei; Swain, Michael; Li, Qing
Abstract Although implant-retained overdenture allows edentulous patients to take higher occlusal forces than the conventional complete dentures, the biomechanical influences have not been explored yet. Clinically, there is limited knowledge and means for predicting localized bone remodelling after denture treatment with and without implant support. By using finite element (FE) analysis, this article provides an in-silico approach to exploring the treatment effects on the oral mucosa and potential resorption of residual ridge under three different denture configurations in a patient-specific manner. Based on cone beam computerized tomography (CBCT) scans, a 3D heterogeneous FE model was created; and the supportive tissue, mucosa, was characterized as a hyperelastic material. A measured occlusal load (63N) was applied onto three virtual models, namely complete denture, two and four implant-retained overdentures. Clinically, the bone resorption was measured after one year in the two implant-retained overdenture treatment. Despite the improved stability and enhanced masticatory function, the implant-retained overdentures demonstrated higher hydrostatic stress in mucosa (43.6 kPa and 39.9 kPa for two and four implants) at the posterior ends of the mandible due to the cantilever effect, than the complete denture (33.4 kPa). Hydrostatic pressure in the mucosa signifies a critical indicator and can be correlated with clinically measured bone resorption, pointing to severer mandibular ridge resorption posteriorly with implant-retained overdentures. This study provides a biomechanical basis for denture treatment planning to improve long-term outcomes with minimal residual ridge resorption.